2020
DOI: 10.1021/acsanm.0c01056
|View full text |Cite
|
Sign up to set email alerts
|

Silanized Liquid-Metal Nanoparticles for Responsive Electronics

Abstract: Room-temperature liquid-metal particles are a burgeoning material platform for stimuli-responsive electronics, self-healing circuitry, stretchable/flexible conductors, drug delivery, and wearable devices. The ability to chemically tune the nanoscale surface oxide of liquid-metal particles is critical to these applications. To this end, a method of silanizing liquid gallium alloy particles has been developed. The benefits of alkoxysilane ligands are demonstrated by orthogonal functionalizations to produce chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 46 publications
0
58
0
Order By: Relevance
“…Prior work on gallium nanoparticles (tens to hundreds of nanometers) has shown that nanoparticle films require force to form a conductive network, and that smaller particles are stiffer than larger particles due to the mechanics of the native oxide skin [ 6 , 45 , 76 , 77 , 78 ]. Meanwhile, work which features metal droplets that are tens to hundreds of microns in diameter are capable of immediately and repeatably forming conductive paths [ 71 , 72 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior work on gallium nanoparticles (tens to hundreds of nanometers) has shown that nanoparticle films require force to form a conductive network, and that smaller particles are stiffer than larger particles due to the mechanics of the native oxide skin [ 6 , 45 , 76 , 77 , 78 ]. Meanwhile, work which features metal droplets that are tens to hundreds of microns in diameter are capable of immediately and repeatably forming conductive paths [ 71 , 72 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…To realize the applications in flexible electronics and biomedicine, nanoparticles with improved performances in yields, stability, small sizes, uniform distribution, and high purity are favored. Many solutions are proposed, including development of dynamic temperature control system, [ 95 ] screening of novel macromolecules, or ligands, such as brushed polyethylene glycol (bPEG), [ 96 ] aliphatic carboxylates with different chain lengths, [ 97 ] phosphonic acids, [ 98 ] alkoxysilane ligands, [ 99 ] and comb‐like polymers. [ 100 ]…”
Section: Synthesis Of Lmnpsmentioning
confidence: 99%
“…[ 111 ] In recent research, Farrell et al proposed the silanization method to decorate the surface of LMNPs, which can provide more possibility for further functionalization and would be useful for drug delivery and development of theranostic platform. [ 99 ]…”
Section: Applications Of Lmnps In Biomedicinementioning
confidence: 99%
“…dodecylphosphonic acid, 11-phosphonoundecanoic acid, silanes) chemically and/or physically bond with the native oxide layer of LM. [109,110] Such surface modifications can tune the thickness of the oxide from 1.28 to 4.46 nm. [109] Due to the increase in oxide skin thickness, elastic modulus increases from 0.37 to 1.38 GPa and also stiffness increases from 0.05 AE 0.03 to 2.90 AE 0.51 N m À1 .…”
Section: Surface Modification Using Ligand Bindingmentioning
confidence: 99%